The Effect Of Work From Home And Work Discipline On The Performance Of BPJS Ketenagakerjaan Medan City Branch - Syahfitri, Khofifah Dwi; Mardhiyah, Ainun (SEAN Institute, 2022)
One of the factors that affect employee performance is the Work From Home (WFH) work system and work discipline, BPJS Ketenagakerjaan Cabang Medan Kota is a public legal entity that implements the WFH policy during 2021 to 2022, In the implementation of WFH there is a problem, namely the decline in target achievement in 2021. This study aims to analyze how the influence of WFH and work discipline on the performance of employees of BPJS Ketenagakerjaan Cabang Medan Kota. The effect of WFH and work discipline was analyzed simultaneously and partially on employee performance. The form of research used is quantitative research with an associative approach. The sample in this study used a saturated sample where there were 50 respondents who were sampled. The data analysis method used is validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that WFH and work discipline had a positive effect partially or simultaneously on employee performance. This means that the better the WFH work system and work discipline, the better the performance of BPJS Ketenagakerjaan Cabang Medan Kota.